MEDIA CONTENT ANALYSIS IN THE PROVINCE OF EAST KALIMANTAN AND PUBLIC PERCEPTION ON THE IMPLEMENTATION CORPORATE SOCIAL RESPONSIBILITY - Rina Juwita (Universitas Padjadjaran, 2013)
The issue of Corporate Social Responsibility is considered as a sensitive issue since itrelates to the company’ contribution to develop and to increase community welfare. However, the conceptof CSR implemented by the corporations is more on carring the image building and social investmentmission made by the public relations division through the mass media. Therefore, this media contentanalysis is conducted to determine the CSR trend reported by the corporate and the media. The analysiswas done quantitatively which are presented in tables and charts, then riched with interviews to refinethe analysis. Based on the research, the CSR news covered is more on the charity/donor/sponsorship,and frequently used as a tool of corporate PR to promote ‘the good things’ that have been undertakenby the companies. The public representative also stated that the CSR news written by the media moreon to promote that the company has done good things for the community. This happens because of thenews only contain info and photos that show the sheer relief only which indicate that the newspaper hasa firm economic independency that creates a situation where the media cannot be actively critic the CSRprograms which have undertaken by the companies.